Exact solutions of some nonlinear partial differential equations - Inan, Ibrahim E.; Kaya, Dogan (Elsevier, 2007)
We implemented a generalized tanh function method for approximating the solution of the combined Korteweg-de Vries (CKdV) equation and Sharma-Tasso-Olver equation. By using this scheme, we found some exact solutions of the CKdV equation and Sharma-Tasso-Olver equation. For the further investigation of the method, some exact solutions of the Boussinesq equation and the complexly coupled KdV equations have been obtained. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: The CKdV-equation; Sharma-Tasso-Olver equation; generalized tanh function method; The boussinesq equation; complexly-coupled; KdV equations; traveling wave solutions